Pengaruh Brand Image Judul Program terhadap Minat Menonton Program Talkshow Tonight Show Net TV - Rizka Aprilliani; Muhammad Gafar Yoedtadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Brand image is the perception and belief held by consumers, such as those in association and embedded in consumers memories. While the notion of interest is the tendency of someone to pay attention to some activities or activities that are liked by individuals. Tonight Shows a program that has an interest in watching the influence of the appearance of the program, and the host of the Tonight Show. This study uses quantitative survey methods for respondents in Taman Royal 2, Tangerang City. The results showed the effect of brand image on the interest in watching the Tonight Show talkshow program, with the results of the correlation coefficient of 0.732. Based on the results of the coefficient of determination test, found the influence of brand image on the interest to watch the Tonight Show talkshow program has a strong influence that is equal to 53.5% and T test results obtained that Ho is rejected and Ha is accepted. Citra merek (brand image) adalah persepsi dan keyakinan yang dipegang oleh konsumen, seperti yang ada dalam asosiasi dan yang tertanam dalam ingatan konsumen. Sedangkan pengertian minat adalah kecenderungan seseorang yang memperhatikan beberapa aktivitas atau kegiatan yang disukai oleh individu. Tonight Show menjadi program acara yang memiliki minat menonton pada pengaruh tampilan acara, dan pembawa acara Tonight Show. Penelitian ini menggunakan kuantitatif dengan metode survey terhadap responden di Taman Royal 2 Kota Tangerang. Hasil penelitian menunjukkan hasil adanya pengaruh brand image terhadap minat menonton program talkshow Tonight Show yang kuat, dengan hasil koefisien korelasi sebesar 0,732. Berdasarkan hasil uji koefisien determinasi, didapati pengaruh brand image terhadap minat untuk menonton program talkshow Tonight Show memiliki pengaruh yang kuat yaitu sebesar 53,5% dan didapatkan hasil uji T bahwa Ho ditolak dan Ha diterima.